Implementation of Sanctions against Addictive and Narcotic Abuse Perspective Restorative Justice - Cok Satrya Aditya; Ani Purwanti (Britain International for Academic Research (BIAR-Publisher), 2023)
Even though there is a law Number 35 Year 2009 about Narcotics, application of sanctions against addicts and abusers narcotics felt not fulfilling the principle of justice. So it is necessary to solve the problem using Restorative justice . The purpose of writing this article is to look at other solutions to imposing sanctions on addicts and abusers narcotics for the sake of creating a sense of justice. The method used is normative legal research using a conceptual approach and legislation. Then the formulation of the problem that the author can raise first is how to apply sanctions to addicts and abuse narcotics in Indonesia. second , how is the application of Restorative Justice in case narcotics in Indonesia. The results of this study indicate that in Indonesia the application of sanctions against addicts and abuse narcotics Not yet in accordance with the principle of justice and efforts to apply sanctions for addicts and abusers narcotics use perspective Restorative Justice exists but has not worked as expected.